Software System for Motion Detection and Tracking - Tsiunyk, B.; Muliarevych, O. (Видавництво Львівської політехніки, 2022)
The goal of the work is to develop a software system for motion detection of and tracking object. It consists of the user interface which is presented as a desktop application. This paper describes the process of developing a desktop software system stage using the latest technologies which will be relevant and easy to maintain in future development and upgrade. The technologies used in the development process, the systems and modules which were integrated into the project, the main approaches to software development, as well as an explanation of why this particular stack of technologies was preferred for the implementation of this software system have been described. To make sure that the developed desktop application meets common optimization requirements it has been tested for resource usage.
Keywords: desktop architecture; development; Open CV; Python